A facilitation between large herbivores and ants accelerates litter decomposition by modifying soil microenvironmental conditions. (7th May 2021) - Li, Xiaofei; Risch, Anita C.; Sanders, Dirk; Liu, Guofang; Prather, Chelse; Wang, Zhongnan; Hassan, Nazim; Gao, Qiang; Wang, Deli; Zhong, Zhiwei
Abstract: Large herbivores and insects commonly coexist and play important functional roles in grassland ecosystems. The interactive effects of these two animal groups in shaping ecosystem processes and functioning are poorly understood. In a semi‐arid grassland of northeastern China, we previously found a reciprocal facilitation between large herbivores (cattle; Bos tarurs ) and ants: cattle grazing led to a twofold increase in ant mound abundance compared with ungrazed sites, while the presence of ant mounds, in turn, increased the foraging of cattle during the peak of the growing season. Here, by using a large‐scale, 4‐year (2010–2013) manipulative experiment, we further investigated how such a facilitation between large herbivores and ants can affect a key ecosystem process, litter decomposition. Using a set of small‐scale reciprocal translocation litterbag experiments, we separated the effects of litter quality and soil microenvironmental factors altered by cattle and ants on litter decomposition rates. A significant interaction between the experimental factors, cattle grazing and ant presence, showed that litter decomposition rate was at the highest levels when both cattle and ants were present, with only a small impact when each was present on its own. Mechanistically, cattle and ants exerted limited effects on litter quality (litter C:N ratio). However, these animals greatly altered soil microenvironments by increasing soil N availability, which in turn increased soil microbial biomass and accelerated decomposition process. Synthesis . Our results demonstrate how positive interactions between two groups of animals, large herbivores and ants, can affect decomposition rates, with important consequences for ecosystem carbon and nutrient cycling. Large herbivores, either domestic or wild, often coexist and interact frequently with a diverse of other fauna in terrestrial ecosystems. Assessing their interactive effects will help us to better understand their role in shaping ecosystem processes and functioning with important management implications. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.